A review on natural cholesterol lowering supplements sold in South African pharmacies - Lee, Hyeon Bok (My University, 2024)
Background: Dyslipidaemia is defined as elevated total or low-density lipoprotein (LDL) levels or low levels of high-density lipoprotein (HDL). Patients may often make use of natural cholesterol lowering supplements (NCLS) available at the pharmacy, however, limited information on these supplements is readily available. Pharmacists should be knowledgeable about NCLSs to ensure that the use of these supplements is supported by evidence and to provide appropriate advice to patients for desirable therapeutic outcomes. Aim: This study aimed to identify the NCLS being sold in South African pharmacies and review the scientific evidence for each of the ingredients in these NCLSs. Methods: Seventeen NCLS products were identified, and the Joanna Briggs Institute (JBI) scoping review methodology was used to conduct a literature review of NCLSs. Results: From the ingredients reviewed it is evident that coenzyme Q10, probiotics, and sterols have sufficient evidence supporting their use. However, there is still limited scientific evidence available to validate the rest of the ingredients. Conclusion: Further research on NCLSs will provide practicing pharmacists and practitioners with a guide to the evidence available on the various ingredients in NCLSs. Contribution: This study provides a review of the available literature on the NCLSs being sold in the pharmacies across South Africa to provide pharmacists with a collated document of the evidence behind these popular supplements to assist them in making evidence based informed decision regarding natural products for cholesterol.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine (Pharmaceutical Affairs) to the Faculty of Health Sciences, University of the Witwatersrand, School of Therapeutic Sciences, Johannesburg, 2023
Keywords: Dyslipidaemia; Supplements; Cholesterol